A Foley Fallacy: A Case of Bladder Rupture after “Routine” Foley Catheter Placement - Shiva Poola; Arjun Mohan (Case Reports in Urology)
Bladder injury is a rare condition mostly due to high-energy trauma. Bladder injury tends to be suspected during traumatic events in the setting of hematuria, pain, and voiding difficulty. Unfortunately, in end-stage renal disease patients who are oliguric or anuric these classic clinical findings would not be seen. We report a case of bladder rupture without a history of trauma or without a history of hematuria or voiding difficulties. To our knowledge this is the first case to describe such an injury with a lack of trauma history.